Urogenital Lesions in Nonhuman Primates at 2 National Primate Research Centers. Issue 1 (January 2021) - Kirejczyk, Shannon; Pinelli, Christopher; Gonzalez, Olga; Kumar, Shyamesh; Dick, Edward; Gumber, Sanjeev
Given their genetic and anatomic similarities to humans, nonhuman primates (NHPs) may serve as animal models for urogenital diseases of humans. The purpose of this study was to examine the frequency of spontaneous urogenital lesions occurring over a 30-year period at the Yerkes and Southwest National Primate Research Centers and to compare and contrast lesions occurring in Old World versus New World primates. Lesions occurring in the chimpanzee ( Pan troglodytes ), baboon ( Papio spp.), rhesus macaque ( Macaca mulatta ), cynomolgus macaque ( Macaca fascicularis ), pig-tailed macaque ( Macaca nemestrina ), sooty mangabey ( Cercocebus atys ), common marmoset ( Callithrix jacchus ), cotton-top tamarin ( Sanguinus oedipus ), and squirrel monkey ( Saimiri sciureus ) are discussed. The most common lesions of the kidney were medullary amyloidosis, renal cysts, renal tubular degeneration, glomerulonephritis or glomerulopathy, nephritis, nephrocalcinosis, pyelonephritis, and hydronephrosis. Specific causes of renal tubular disease included pigmentary nephrosis and tubular lipidosis. Renal tumors, including renal adenoma and carcinoma, lymphoma, and nephroblastoma, were infrequent diagnoses in all species. Endometriosis was the most frequently diagnosed lesion of the female genital tract. Of the animals examined in this study, it was most frequent in Old World primates. Leiomyoma was the most common uterine tumor. Granulosa cell tumor was the most frequently observed neoplasm of the ovaries, followed by teratoma. Of animals included in the study, most ovarian tumors occurred in baboons. Neoplasms of the male reproductive tract included interstitial cell tumor, seminoma, penile squamous cell carcinoma, penile papilloma, and histiocytoma. In New World monkeys, renal lesions were reported more frequently than genital lesions.